The search for supersymmetry in complex hadronic states using the ATLAS detector - O'Neill, AP (2021)
The standard model of particle physics is incomplete. A well motivated solution to several of its issues, including the absence of dark matter, is a theoretical extension called supersymmetry. Supersymmetric particles may be produced in the 13 TeV collisions recorded by the ATLAS experiment at the LHC. The presence of a dark matter candidate particle would be signified by the presence of missing transverse momentum, MET, in an event. A quantity designed to find very weakly interacting particles escaping the detector. This thesis first analyses the performance of MET and its significance with the complete ATLAS p-p Run 2 dataset with a centre of mass energy of 13 TeV.